Pengaruh Gaya Kepemimpinan Participative Terhadap Prestasi Kerja Dan Kinerja Karyawan Pada PT Hero Supermarket TBK. Bintaro Divisi Sales Support - Inge Pratiwi; P. Helen Widjaja; Christina Catur Widayati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to examine and analyze the influence of participative leadership style on employee performance dan performance. The research method used in this research is descriptive method. This research object is employee sales support division of PT Hero Supermarket Tbk. Bintaro with a population of 70 people. The sampling technique used a saturated sample with a sample size of 70 people. The approach used in this research is structural equation model (SEM) with Smart-PLS analysis. The result of this study show participative leadership style has a positive and significant impact on work performance. Participative leadership style has a positive and significant impact on employee performance.